2007
DOI: 10.1080/01904160701700558
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Rice Genotypes Tolerant to Zinc Deficiency and Sodicity: Differences in Concentration of Major Cations and Sodium/Potassium Ratio in Leaves

Abstract: Zinc (Zn) deficiency is a major nutritional problem for rice under sodic conditions. Seedlings (35-d old) of 30 rice genotypes were transplanted in pots at pH 2 9.8 [diethylene triamine penta acetic acid (DTPA) Zn 1.8 ppm] to identify genotypes tolerant to both sodicity and Zn deficiency. Ten genotypes (group A) showed potential to tolerate both the stresses. Sixteen genotypes (group B) were sensitive to Zn deficiency. However, some of the seedlings of group B genotypes were normal (without Zn deficiency sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…K nutrition ameliorated to a great extent the Na + and Cl --accrued decrease in reducing equivalents viz., AsA and GSH which, in turn, had a tight control over the balance between production and scavenging of H 2 O 2 and stabilized the cell membrane by decreasing TBARS content through coordination with other components of the AsA-GSH cycle. Our findings that K nutrition improves the leaf K + and decreases the Na + and Cl -contents confirm those of Qadar and Azam [10], Zheng et al [40,45] and More and Manchanda [39].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…K nutrition ameliorated to a great extent the Na + and Cl --accrued decrease in reducing equivalents viz., AsA and GSH which, in turn, had a tight control over the balance between production and scavenging of H 2 O 2 and stabilized the cell membrane by decreasing TBARS content through coordination with other components of the AsA-GSH cycle. Our findings that K nutrition improves the leaf K + and decreases the Na + and Cl -contents confirm those of Qadar and Azam [10], Zheng et al [40,45] and More and Manchanda [39].…”
Section: Discussionsupporting
confidence: 80%
“…In this context, we have shown that the addition of K to the NaCl-treated plants proved to be effective in protecting B. campestris plants against NaCl-caused oxidative stress by decreasing Na + and Cl -content and increasing K + in leaves. The antagonistic effect of K + and Na + on uptake of each other is well documented and reported in both saline and sodic conditions [10,27,39,40]. Added K also improved AsA and GSH contents, and further enhanced the activity of APX and GR, whereas the activity of SOD dropped with K-supplementation to the NaCl-treated plants.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation